A REVIEW: SUSTAINABLE DEVELOPMENT OF MANUFACTURING UNIT THROUGH FACILITY LOCATION PLANNING IN PLANT LAYOUT - Prem Narayan Ahirwar, Dr. V.K.Khare & Dr. Pankaj Agarwal (International Journal of Research Science and Management, 2017)
Facility location planning method play a crucial role in specifying the optimum location options for various types of Facilities Location. Facilities design consists of the facility systems design, the layout the environmental systems, the lighting-electrical systems and safety systems. The layout consists of all equipment, machinery and furnishings within the building structure Sustainable development requires implementing suitable policies integrating several competing objectives on economic, environmental, energy and social criteria. This paper serves as a discussion of the current literature concerning the sustainability aspects of the location problem. The main motivation for the current study is to provide a foundation from which issues of sustainable development can be built into facility location models. This paper focused on the modification of the existing layout location planning.